Monitoring and Analysis of Soil Moisture in Critical Growth Period of Summer Harvest Crops in Yongnian District - LAI Bin; DONG Sen; YANG Haiyan; HE Shuai; ZHOU Wei; SUN Congwu (Renmin Zhujiang)
In order to research the spatial-temporal change of soil moisture during the critical growth period of summer harvest crops in North China, this paper designs a high-frequency regional soil moisture monitoring experiment, implements the experiment from April 28 to May 21, 2019 in Yongnian District, Hebei, and analyzes the spatial change by Kriging interpolation method based on measured data. The results indicate that: The soil moisture in the eastern part is higher than that in the western part during the critical growth of regional summer harvest crops, the soil moisture of garlic planting area is higher than that of winter wheat; Moisture in 0~20 cm soil layer shows significant dynamic and porphyritic characteristics in time and space, while the moisture in 20~40 cm soil layer is highly similar to that of 40~60 cm soil layer in time and space; The irrigation time during critical growth period of summer harvest crops in Yongnian district is early May, and the regional soil moisture changes slowly after mid-May. The crops enter a mature period. The research results can provide reference for the change of soil moisture in the critical growth period of regional summer harvest crops and the irrigation water management.